(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The above quoted statement by the famous Russian author, Alexander Solzhenitsyn, can to my opinion be interpreted as a dream of revitalization of good, old Russian virtues, which the communist regime had silenced and placed in the corner. Then I reflected on the status of virtues in my own country, and especially what history education had done to stick to virtues, which I have encountered in my earlier research as dominant in the 18th century educational discourse? My provisional examinations are presented in this article, where I focus on the impact of virtues in a sample of more popular Danish history textbooks over three centuries. Research in textbooks is closely connected to the societal context and a brief summary of the development in Denmark since the Enlightenment is appropriate, especially for the foreign reader, in order to understand the textbooks in a proper context. In the 18th century the Danish king was the absolute ruler of Denmark, Norway and the North Atlantic islands. Moreover he was the sovereign in the deuces Schleswig and Holstein and of course in the colonies in India, Africa and Caribbean. This multicultural state was transformed in the 19th century; in 1814 Norway was ceded to Sweden, and in 1864 Schleswig and Holstein were after a bloody war, taken over by Prussia. Hence Denmark was one of the smaller countries in Europe, however now a national state. In 1814 compulsory sevenyear school attendance was implemented for all girls and boys, and in the second half of the century agriculture and industry underwent a remarkable growth. In 1849 the absolute ruling king signed a constitution, which introduced partial democratic elections. Although literacy was acquired by nearly all Danish children, the development of secondary education was slow, illustrated by the fact that only 89 students in 1849 finished their upper secondary education in the Kingdom of Denmark. In 1921 it rose to nearly 2% of a year group, whereas today 75 %, equivalent to 60.000 teenagers are prepared for further studies. The upper secondary education also consisted of lower secondary schools, which prepared the students for trade and public services. Over the three centuries history education was mandatory for all upper secondary students. In this article I shall give some provisional answers to the questions: What happened to virtues in history textbooks over 300 years and why?